Radiative forcing by light-absorbing particles in snow. Issue 11 (November 2018) - Skiles, S.; Flanner, Mark; Cook, Joseph; Dumont, Marie; Painter, Thomas
Abstract As one of the brightest natural surfaces on Earth, the darkening of snow by light-absorbing particles (LAPs) — dust, black carbon or microbial growth — can trigger albedo feedbacks and accelerate snowmelt. Indeed, an increase in black carbon deposition following the industrial revolution has led to the recognition that LAP radiative forcing has contributed to a reduction in the global cryosphere, with corresponding climatic impacts. This Review synthesizes our current understanding of the distribution of radiative forcing by LAPs in snow, and discusses the challenges that need to be overcome to constrain global impacts, including the limited scope of local-scale observations, limitations of remote sensing technology and the representation of LAP-related processes in Earth system models. Snow albedo is impacted by the presence of light-absorbing particles, including black carbon and dust. This Review collates knowledge on the associated radiative forcing, discussing geographic variability, future impacts and challenges for reducing uncertainty.